Polysaccharides synergistic boosting drug loading for reduction pesticide dosage and improve its efficiency. (1st December 2022) - Fan, Chaoran; Liu, Yan; Dang, Minfei; Liang, Yuntong; Feng, Pu; Wei, Fuxiang; Fu, Lihua; Xu, Cuanhui; Lin, Baofeng
Abstract: Overuse of pesticides is an urgent issue to be solved in sustainable agriculture. Based on the synergistic drug loading effect of β-cyclodextrin (β-CD) encapsulation and alginate (Alg) cross-linking, a new environment-responsive drug delivery system (TMX-loaded Alg/β-CD) was constructed. The relationship between carrier structure and solubility of thiamethoxam (TMX) was researched by molecular simulation. β-CD has good binding affinity with TMX, which can increase TMX solubility by 40 %. Further co-loading with alginate could double the drug loading of the cyclodextrin inclusion complex up to 41 %. TMX-loaded Alg/β-CD exhibits excellent environment-responsive controlled-release performance, and TMX sustained release time is 7.5 times longer than that of commercial agents. The pest control efficacy of TMX-loaded Alg/β-CD is 20 days longer than that of commercial TMX, and the crops has no pesticide residues after using. This study provides a promising strategy for the commercial application of polysaccharide in pest control and pesticide reduction. Graphical abstract: A high drug loading, environmental response and long-term pest control pesticide carrier based on β-cyclodextrin/alginate for pesticide reduction and increase efficiency in field trials. Unlabelled Image Highlights: First field validation experiment of a polysaccharide complex delivery system. Improving the water solubility and loading of pesticides through co-loading. Combining molecular simulations to study the interaction of TMX with β-CD. The effects of various environmental factors on release were systematically studied. In field trials, pest control was 20 days longer than commercial pesticides.